2014
DOI: 10.1080/03235408.2013.877192
|View full text |Cite
|
Sign up to set email alerts
|

Host specificity, pathogenicity and the presence of virulence genes in Iranian strains ofPseudomonas syringaepv.syringaefrom different hosts

Abstract: Pseudomonas syringae pv. syringae (Pss) strains were isolated from almond, apricot, peach, pear, sweet cheery and wheat in Kohgiluye and Boyer-Ahmad, Kordestan, Fras and Chaharmahal and Bakhtiari provinces of Iran. The strains were examined for host specificity, the presence of virulence genes and pathogenicity on different hosts. After inoculation of isolates, in compatible reactions bacterial populations increased within six days of inoculation and final cell numbers increased several-fold over initial inocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…If this pathogenic strategy has evolved in the P2 clade, it raises the question as to how it affects host specificity and virulence. P2 strains often infect more than one host species (Rezaei & Taghavi, ). These strains probably possess fewer ETI‐inducing avirulence factors that restrict effector‐rich strains to particular hosts, so may be more successful generalists.…”
Section: Discussionmentioning
confidence: 99%
“…If this pathogenic strategy has evolved in the P2 clade, it raises the question as to how it affects host specificity and virulence. P2 strains often infect more than one host species (Rezaei & Taghavi, ). These strains probably possess fewer ETI‐inducing avirulence factors that restrict effector‐rich strains to particular hosts, so may be more successful generalists.…”
Section: Discussionmentioning
confidence: 99%
“…If this pathogenic strategy has evolved in the P2 clade, this raises the question as to how it affects host specificity and virulence. P2 strains often infect more than one host species (Rezaei & Taghavi, 2014). These strains probably possess fewer ETI-inducing avirulence factors that restrict effector-rich strains to particular hosts, so may be more successful generalists.…”
Section: Discussionmentioning
confidence: 99%
“…A host specificity study on cucurbits showed remarkable variation in the virulence of phylogroup 2 strains on two different host species (Newberry et al, 2019), which was postulated to be due to differences in effector repertoires. Another study by Rezaei and Taghavi (2014)…”
Section: Diverse Weaponry Leads To Pathogenicitymentioning
confidence: 99%
“…The designation of strains as pathovar syringae (i.e., Pss) within phylogroup 2 provides no information about their host range or symptoms produced, and ignores genetic diversity. In terms of host specificity, closely related strains of Pss have been isolated from different Prunus species, such as apricot, cherry, and plum and many can cross-infect (Gilbert et al, 2008;Rezaei and Taghavi, 2014;Hulin et al, 2018b). Members of the other Prunus-infecting clades may be more host-restricted.…”
Section: Phylog Ene Tic S Re Ve Al S Converg Ent E Volutionmentioning
confidence: 99%